Torsemide Versus Furosemide in Heart Failure Patients: Insights From Duke University Hospital. Issue 5 (May 2015) - Mentz, Robert J.; Buggey, Jonathan; Fiuzat, Mona; Ersbøll, Mads K.; Schulte, Phillip J.; DeVore, Adam D.; Eisenstein, Eric L.; Anstrom, Kevin J.; O'Connor, Christopher M.; Velazquez, Eric J.
Abstract : Abstract: Furosemide has historically been the primary loop diuretic in heart failure patients despite data suggesting potential advantages with torsemide. We used the Duke Echocardiography Lab Database to investigate patients admitted with heart failure to Duke Hospital from 2000 to 2010 who were discharged on either torsemide or furosemide. We described baseline characteristics based on discharge diuretic and assessed the relationship with all-cause mortality through 5 years. Of 4580 patients, 86% (n = 3955) received furosemide and 14% (n = 625) received torsemide. Patients receiving torsemide were more likely to be female and had more comorbidities compared with furosemide-treated patients. Survival was worse in torsemide-treated patients [5-year Kaplan–Meier estimated survival of 41.4% (95% CI: 36.7–46.0) vs. 51.5% (95% CI: 49.8–53.1)]. After risk adjustment, torsemide use was no longer associated with increased mortality (hazard ratio 1.16; 95% CI: 0.98–1.38; P = 0.0864). Prospective trials are needed to investigate the effect of torsemide versus furosemide because of the potential for residual confounding.